TRABAJO COMUNAL ESTUDIANTIL EN LA COMUNIDAD DE RÍO JESÚS, SAN RAMÓN, ALAJUELA (Biocenosis, 2015)
This article describes the activities undertaken as part of the Community Universitary Work called Demonstrative Forest in the Sede Occidente of the University of Costa Rica. Such actions propitiate participants take ownership of the natural sciences in the targeted communities of the project, such as Rio Jesus. The people of this community were pleased to have participated in a reforestation journey and an Environmental Education Fair where forest and water conservation were favored. Environmental Fair; Reforestation; Education; School; Recreation
Keywords: Environmental Fair; Reforestation; Education; School; Recreation